Die invloed van kouebehandeling en fotoperiode op fotosintese by koring - Joubert, G. D.(Gideon Daniel) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD (Agric)) -- University of Stellenbosch, 1974.